Revision of the cicada genus Dilobopyga (Hemiptera, Cicadidae) from Sulawesi and the Moluccas - Duffels, J.p. (Zootaxa, 2018)
This revision of the cicadas of the genus Dilobopyga provides a diagnosis of the genus and descriptions, illustrations and distribution maps for 48 species. The following 33 species described here are new to science: D. angulata, angustata, bifida, curvispina, fasciata, hayashii, hollowayi, johani, knighti, langeraki, laterocurvata, latifascia, luwukensis, macrocerata, maleo, mamasa, mediolobata, nebulosa, operculata, palopoensis, pelengensis, platyacantha, quadrimaculata, rantemario, recurvata, rozendaali, sangihensis, sarasinorum, splendida, tambusisi, toraja, vantoli and watuwila. The key presented is designed for the identification of males of Dilobopyga to the species level. The subdivision of the genus in five species groups viz., opercularis group (17 species), nebulosa group (1 species), chlorogaster group (16 species), minahassae group (6 species) and watuwila group (8 species), is sustained by a phylogenetic analysis of morphological characters of all species described. The cicadas of the genus Dilobopyga are found in Sulawesi, neighbouring islands and southern Moluccas. Of the 48 species of Dilobopyga 43 species are endemic to Sulawesi. Most of these Sulawesi species are restricted to either one peninsula or to a part of Central Sulawesi. The remaining five species are endemic to either the Sangihe Islands, Banggai Islands or the southern Moluccas. A taxon-area cladogram for the species of Dilobopyga provides a basis for a discussion on the historic biogeography of the genus.